Perbedaan ekspresi Vascular Endothelial Growth Factor (VEGF) pada meningioma risiko rendah dan risiko tinggi di RSUP Sanglah, Bali, Indonesia - Ivana Juliarty Sitanggang; Ni Putu Sriwidyani; I Wayan Juli Sumadi; I Gusti Ayu Sri Mahendra Dewi; Luh Putu Iin Indrayani Maker; I Made Muliarta (Intisari Sains Medis, 2021)
Background: Vascular Endothelial Growth Factor (VEGF) is an angiogenic factor that plays an important role in tumor angiogenesis. VEGF in meningioma is up-regulated and indicates its role as a proangiogenic factor. It has an association with tumor recurrence and progression. This study aims to determine the differences in VEGF expression in low-risk and high-risk meningiomas at Sanglah General Hospital, Bali, Indonesia.Methods: This study was a cross-sectional analytical study with a sample size of 52, which came from meningioma patients examined histopathologically at the Anatomical Pathology Laboratory of Sanglah General Hospital from January to December 2019. The VEGF immunohistochemical staining was performed and interpreted using Histo score (H-score). VEGF expression was categorized into high and low expression, with the cut-off value determined based on the median value. Data were analyzed using SPSS version 20 for Windows.Methods: The results showed that out of 52 meningioma samples, 37 (71.1%) cases of low-risk meningiomas with low VEGF expression, 6 cases (11.5%) of low-risk meningiomas with high VEGF expression, and 9 cases (17.3%) of high-risk meningiomas with high VEGF expression. There was no high-risk meningioma with low VEGF expression. There was a significant difference in VEGF expression between the low-risk and high-risk meningioma groups (p = 0.00), and high VEGF expression had a prevalence risk for the incidence of high-risk meningioma by 2.5 times (95% CI=1.3-4.6).Conclusion: Based on the results of this study, it was concluded that there was a VEGF expression difference between low-risk and high-risk meningiomas in Sanglah General Hospital Denpasar and high VEGF had a prevalence risk for the occurrence of high-risk meningiomas by 2.5 times. Latar Belakang: Vascular Endothelial Growth Factor (VEGF) merupakan faktor angiogenik yang berperan penting dalam angiogenesis tumor. VEGF pada meningioma mengalami up-regulation yang menunjukkan perannya sebagai faktor proangiogenik yang berkaitan dengan rekurensi dan perkembangan tumor. Penelitian ini bertujuan untuk menentukan perbedaan ekspresi VEGF pada meningioma risiko rendah dan risiko tinggi di RSUP Sanglah, Bali, Indonesia.Metode: Penelitian ini merupakan studi analitik potong lintang dengan besar sampel adalah 52, yang berasal dari blok parafin penderita meningioma yang diperiksa histopatologi di Laboratorium Patologi Anatomi RSUP Sanglah Denpasar dari Januari - Desember 2019. Dilakukan pulasan imunohistokimia VEGF dan penilaiannya menggunakan Histo score (H-score). Ekspresi VEGF dikategorikan menjadi tinggi dan rendah dengan nilai cut-off yang ditentukan berdasarkan nilai median. Data dianalisis dengan SPSS versi 20 untuk Windows.Hasil: Hasil penelitian ini menunjukkan bahwa dari 52 sampel meningioma, terdapat 37 kasus (71,1%) meningioma risiko rendah dengan ekspresi VEGF rendah, 6 kasus (11,5%) meningioma risiko rendah dengan ekspresi VEGF yang tinggi, dan 9 kasus (17,3%) meningioma risiko tinggi dengan ekspresi VEGF tinggi. Tidak didapatkan meningioma risiko rendah dengan ekspresi VEGF rendah. Didapatkan perbedaan ekspresi VEGF yang bermakna antara kelompok meningioma risiko rendah dan risiko tinggi (p=0,00) dan ekspresi VEGF tinggi mempunyai risiko prevalensi untuk terjadinya meningioma risiko tinggi sebesar 2,5 kali (95% IK=1,3-4,6).Kesimpulan: Berdasarkan hasil penelitian ini didapatkan perbedaan ekspresi VEGF antara meningioma risiko rendah dan risiko tinggi di RSUP Sanglah Denpasar dan pada VEGF tinggi mempunyai risiko prevalensi untuk terjadinya meningioma risiko tinggi sebesar 2,5 kali.